Emerging Technologies in Kenya: A Landscape Analysis 2022 - Ogot, Madara; Guchu, Salome; Muthee, Margaret Wamuyu; Muriuki, Rita (University of Nairobi, 2022)
Emerging technologies (ETs) have been transformative around the world, and Kenya has not been left behind. Indeed, ETs have enabled Kenya to leapfrog legacy infrastructure systems, generate economic growth and promote social inclusion for citizens. There are numerous definitions of what constitutes an Emerging Technology (ET). This study adopts the definition by Rotolo and Martin who defined ET “as a radically novel and relatively fast- growing technology characterised by a certain degree of coherence persisting over time and with potential to exert a considerable impact on the socio-economic domain(s) which is observed in terms of the composition of actors, institutions and patterns of interactions among those, along with the associated knowledge production processes. Its most prominent impact, however, lies in the future, and so at the emergence phase is still somewhat uncertain and ambiguous.” This report presents the results of a study that sought to gain a deep understanding of the emerging technology ecosystem in Kenya. It encompassed an investigation into the landscape and context, enabling factors, risks, opportunities, and early precedents being set on use cases, governance, and the enabling (or not) environment. The overall objective of the study was achieved through the following two specific objectives: 1) to provide an in-depth analysis of the ETs landscape in Kenya; and 2) to identify the key gaps in ETs and recommend opportunities for bilateral and/or multilateral partnerships between Kenya, South Africa and the UK. Both objectives were achieved using a five-dimensional maturity model of the ETs ecosystem in Kenya. Three stages of maturity were defined: ideation, nascent, and growing. The characteristics of the three stages of maturity were based on five fundamental activities, namely education, research, end-use, linkages and implementation. The model formed the basis for the analysis and determination of the stage of maturity of the collective and the individual ETs ecosystems. The study identified seven primary ETs in Kenya’s landscape, namely, artificial intelligence (AI), blockchain, internet of things (IoT), big data/data analytics, geographic information systems (GIS), biotechnology, and nanotechnology. The identified ETs have a significant impact on several sectors of the economy, including agriculture, education, financial services/business, health, information, communication and technology (ICT), and water and sanitation. The key actors were categorised by the role they play within the five fundamental activities. Regulating ET remains a complex phenomenon given the need to mitigate associated risks while at the same time promoting innovation and maximising benefits for all. For emerging digital technologies, for example, the Government is following an approach that takes into consideration how best to protect citizens, ensure fair markets, and enforce regulations while at the same time enabling the technologies and businesses to thrive. The approach is one of:2 Adaptive regulation - Shift from “regulate and forget” to a responsive, interactive approach; Regulatory sandboxes - Prototype and test new approaches by creating sandboxes and accelerators; Outcome- based regulation - Focus on results and performance rather than form; Risk-weighted regulation - Move from one-size-fits-all regulation to a data-driven, segmented approach; and Collaborative regulation - Align regulation nationally and internationally by engaging a broader set of players across the ecosystem. Overall, the ETs ecosystem in Kenya was found to be between the nascent and growth stage of maturity, based on the analysis of each of the fundamental activities and the roles played by each of the actors. Looking at each of the fundamental activities, the education and linkages dimensions were found to be at the nascent stage of maturity. The ET ecosystems were further analysed as three distinct ecosystems – biotechnology, nanotechnology, and emerging digital technologies (AI, IoT, blockchain, big data/data analytics and GIS). The gaps identified at this level also provided for specific areas of potential collaboration between Kenya, South Africa and the UK at each of the fundamental activities within the three distinct ecosystems. Broadly, the key potential areas of collaboration in ETs are in capacity building, Joint research programs, technology transfer, innovation and policy accelerator programs, and academia-business community forums.
Keywords: Emerging Technologies; Kenya; AI; Artifical Intelligence; Digital Technologies; Nanotechnology; Biotechnology